High resolution melting assay in discrimination of the main etiologic agents of leishmaniasis in Iran - Shima Fayaz (Iranian Journal of Microbiology, 2021)
Background and Objectives: The three old world Leishmania species i.e., L. major, L. tropica, and L. infantum are considered as potential etiological agents of the various clinical forms of leishmaniasis in Iran. Different species co-exist in some areas. Accurate differentiation between the species is essential for choosing an appropriate therapy. Conventional and gold standard methods for the detection and characterization of parasites are time-consuming, laborious, and have low sensitivity. A polymerase chain reaction followed by high resolution melting (PCR-HRM) analysis has been employed for detection and species identification. Most of the studies suffer from the use of multiple targets and/ or requiring more than one reaction to identify a single sample. The present study aimed to design a PCR method based on the amplification of kinetoplast DNA minicircles (kDNA) and HRM analysis of the amplicons for rapid discrimination of the three mentioned species. Materials and Methods: DNA from reference strains including L. major, L. tropica, and L. infantum and fifty-eight strains subjected to PCR-HRM analysis targeting kDNA. All the samples were also analyzed by conventional kDNA- PCR. Results: The PCR-HRM analysis allowed discrimination between the three Old World species. The normalized HRM curves for the amplicons of kDNA indicated a unique and repeatable melting plot for each species, even in combination with human and mouse genomic DNA. Conventional kDNA- PCR could not properly discriminate L. tropica from L. infantum. Conclusion: PCR- HRM analysis of kDNA proved to be fast and accurate for discrimination of L. major, L. tropica, and L. infantum.